EXPLORATORY BEHAVIOR ALTERATION AS AN EPILEPTIC COMORBIDITY IN ELEVATED PLUS MAZE TEST - Ademović, Anida; Leković, Aleksa; Knežević, Božo; Grubač, Željko; Šutulović, Nikola; Hrnčić, Dragan; Stanojlović, Olivera (Medicinski podmladak, 2017)
Introduction: Epilepsy is a common neurological disorder, consisted of epileptic seizures. Postictal period is characterized by a variety of psychiatric phenomenon of which the most frequent ones are anxiety and depressive disorder. Exploratory behavior can be used in rodents to assess the presentation of anxiety. Lindane is organochorine, lypophilic substance that can evoke generalized tonic-clonic seizures when it is applied intraperitoneally. Aim: of this study was to measure rat exploratory behavior linked with anxiety level in the elevated plus maze (EPM) test upon generalized seizures induced by lindane. Material and methods: Experiment was conducted on Wistar albino male rats randomly divided to: control (DMSO, 0.5 ml/kg) and experimental (lindane, 8 mg/kg) group (n=8, per each). After the drug injection, the assessment of the seizure intensity took place for 30 minutes. Descriptive rating scale was used to describe the seizure severity. Subsequently, the EPM test took place immediately after evoking the seizure (Test 1), 1h (Test 2) and 24h (Test 3). Time spent in an open areas and number of transitions were further analyzed. Results: Experimental group of animals spent less time in open areas of EPM compared to their controls in Test 1 and Test 2. The same holds true for the number of transitions to the open area, i.e. lindane-treated animals tend to stay in enclosed parts in Test1, Test 2. Finally, in Test 3 there was no significant difference between the groups in all parameters of interest, meaning that anxiety-related behavior lasted for less than 24h. Conclusion: Lindane-induced generalized epileptic seizures are accompanied by reduced exploratory behavior in the elevated plus maze test, what can be a basis for the further translational research of anxiety as epileptic comorbidity in this experimental model of epilepsy. Keywords: anxiety-related behavior, elevated plus maze, lindane, rats